Monitoring of metabolism perturbation in prostate PC-3 cancer cells by sub-lethal concentrations of methotrexate. Issue 1 (2010) - Derenne Derenne, Allison Allison; Gasper Gasper, Régis Régis; Goormaghtigh Goormaghtigh, Erik Erik
Abstract : Infrared imaging was used to investigate the effect of sub-lethal concentration of methotrexate on prostate PC-3 cancer cells. Cells were exposed for 0, 24 and 48 h to 9 nM of methotrexate, the concentration that inhibits 50% of cell growth after 72 h. Sub-lethal concentrations of methotrexate induced a reproducible signature that can be measured by infrared spectroscopy. Student t-test revealed that the process occurs in at least two steps, the first one affecting the nucleic acid region of the spectrum and the second one, the protein region. Imaging of individual cells demonstrated that the recorded differences are not due to a specific subpopulation of cells but homogenously affects all the cells. Near perfect identification of treated cells could be obtained using a supervised classification.